Catholic and reformed traditions in international law : a comparison between the Suarezian and the Grotian concept of Ius Gentium /: a comparison between the Suarezian and the Grotian concept of Ius Gentium. ([2017]) - Macedo, Paulo Emílio Vauthier Borges de
No abstract available